ZWR: Combining wear‐leveling with reclamation for flash‐memory‐based storage systems of embedded systems. Issue 4 (7th February 2017) - Yang, Yin; Sandeep, Subhoyt
Abstract : Flash memory is widely adopted in embedded applications since it has several unique advantages. However, due to its hardware characteristic, uneven erasing and inefficient reclamation have been major concerns. These may not only severely degrade the overall performance but also damage the reliability. In order to solve these problems, we propose a novel scheme, which we call ZWR, for zoning, wear‐leveling, and reclamation. The storage zone is divided into the following three levels: an active zone for storing hot data, an inactive zone for storing cold data, and a transitional zone for storing the reclamation block. A function layer and a flash transformation layer are added to flash memory, which are located between the memory technology device layer and the file system. According to the combined wear‐leveling and efficient reclamation, in the function layer, the erase–write cycles are evenly distributed around the entire flash devices and the invalid blocks can be reclaimed properly. Finally, we implement an accurate flash simulator to evaluate the efficacy of ZWR and compare it with those of other flash schemes. We demonstrate that ZWR can effectively solve uneven erasing and inefficient reclamation problems. It can also greatly prolong the service life of flash devices and improve the efficiency of the erasing operation of blocks. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.